The Legacy of the Monographic Method in Lithuania - Žvinklienė, Alina; Kublickienė, Lilija (Eastern European Countryside, 2024)
This article attempted to overview the use of the monographic method in socio- logical research of Lithuania. Historically, the monographic method stimulated the development of rural sociology in Eastern European countries. The fulfilment of the aim is inevitably related to a question about institutionalisation and the development of sociology and such a sub-discipline as rural sociology in Lithuania. The outcomes of the inquiry allow one to argue that the monographic method is in oblivion rather than in active use, belonging to the history of sociological research in Lithuania. However, the monographic method, often unnamed, is widely applied to contemporary local history research. The geopolitical reasons had a significant impact on retardation in the institutionalisation and development of national sociology. The politics of national identity management, including those of science and education, can be among the important reasons for the absence of institutionalised rural sociology in Lithuania. However, a national social demographical context determining the permanent public and political need “to solve a peasant question” created the bulk of applied research in the Lithuanian countryside that can be considered as adequate data in the frame of rural sociology.